Effect of Peer Tutoring On Students’ Knowledge Retention In Office Technology And Management In Polytechnics In South West, Nigeria. - Ehirheme, Pauline Egberanmwen; Eze, Titus .I (Advances in Social Sciences Research Journal, 2020)
Academic knowledge and transfer of knowledge retention after graduation to the workplace by office technology and management (OTM) students in Polytechnics has been worrisome to stakeholders in education. This study seeks to determine if peer tutoring instructional technique could solve these aforementioned problems. The study adopted a quasi-experimental design of a pre-test, post-test and delayed posttest (knowledge retention) for non-randomized un-equal two groups. The population for the study is 503 National Diploma (ND) II OTM students in four Polytechnics in South West, Nigeria. Through purposive sampling, we selected a sample of 227 (120 experimental and 107 control) students from two polytechnics in two states. These instruments; lesson plan for the experimental group, lesson plan for the control group and Office Technology and Management Achievement Test (OTMAT), were used for data collection. Three OTM experts validated the instruments. The reliability coefficient of the OTMAT was established as 0.86 through the use of Kuder-Richardson formula 21 techniques. Mean and standard deviation were used to answer the research question while Analysis of Covariance (ANCOVA) was used to test the hypothesis. Results revealed knowledge gain for the experimental group. Thus, peer-tutoring enhances academic knowledge retention among OTM polytechnic students. It is therefore recommended that peer-tutoring instructional technique be used to teach OTM students in Polytechnics. Stakeholders should create platforms (workshops and conferences) for OTM lecturers and students in Polytechnics to utilize the peer-tutoring technique in the teaching/learning process.